Rational Use of Fresh Water as a Guarantee of Agribusiness Development in the Context of the Exacerbated Climate Crisis - Dvigun, A.; Datsii, O.; Levchenko, N.; Shyshkanova , G.; Dmytrenko , R. (Science and Innovation, 2024)
Introduction. The global problem of the 21st century is general planetary climate change whose direct consequences are significant warming as well as increasing water shortage and desertification of territories, which together has a merciless impact on agriculture and, subsequently, on the development of agricultural business. Problem Statement. The rational use of fresh water and water supply for agribusiness in arid, dry, and very dry regions of Ukraine, as well as the determination of the priority vectors of its adaptation to climate change, which ensure water and food security of future generations and the environment preservation are the problems to be discussed in this publication. Purpose. The purpose of this research is determining the rational use of fresh water based on the study of foreign experience, the vectors of adaptation of agribusiness to climate change, and the strategy and tactics of its water supply in medium- and long-term horizons. Materials and Methods. In the course of the research, we have used the following methods: the economic and mathematical modelling, while determining the dependence of water use for irrigation on the average monthly air temperature and the average monthly precipitation; forecasting, for determining the volume of water use for irrigation under the condition of modernization of irrigation technologies; the method of analogies, while studying the foreign experience and the possibility of its implementation in domestic practice; monograph, for presenting the research results; abstract and logical methods, for generalizing and formulating conclusions. Results. The priority vectors of agribusiness adaptation to climate change in the regions of the steppe zone of Ukraine have been determined. Conclusions. The study of foreign experience in the rational use of fresh water has enabled us to determine the priority vectors of adaptation of agribusiness to climate change, and hence the strategy and tactics of its water supply on medium- and long-time horizons.